Determination of elements (Cd, Cu, Fe, Pb and Zn) in Universiti Teknologi MARA (UiTM) hostel Shah Alam, Malaysia / Nurzulaifa Shaheera Erne Mohd Yasim, Siti Khadijah Mat Yaacob and Noradila Mohamed. - Mohd Yasim, Nurzulaifa Shaheera Erne; Mat Yaacob, Siti Khadijah; Mohamed, Noradila (2018)
The purpose of this study is to determine the concentration of the selected elemental composition in a multi-storey hostel. Dust samples were taken from three random rooms at each level of the student hostel by sweeping the floor. The concentrations of elements (Cd, Cu, Fe, Pb and Zn) were determined by using Inductively Coupled Plasma-Optical Emission Spectrometer (ICPOES) after digestion with nitric acid and sulfuric acid solutions. Dust samples analysis has shown the different levels of sampling point does not affect the concentration of the elements. The concentration of elements in investigated microenvironment was in the order of Fe > Zn > Cu > Pb > Cd. The correlation analysis was applied to elements variable in order to identify the sources of an airborne contaminant. It was discovered the strong positive correlation between Cu-Zn which indicates the sources come from traffic emission and street dust. This result was supported by the Principal Component Analysis (PCA) that revealed the presence of elements in the student hostel originated from the outdoor sources.